2011
DOI: 10.1038/bmt.2011.88
|View full text |Cite
|
Sign up to set email alerts
|

Treosulfan-based conditioning before hematopoietic SCT: more than a BU look-alike

Abstract: Allogeneic hematopoietic SCT is a curative treatment for a variety of hematological malignancies and genetic diseases. There is a continuous search for novel conditioning regimens that will reduce SCT-related toxicity while retaining maximal antimalignancy effect. Treosulfan (L-threitol-1,4-bis-methanesulfonate; dihydroxybusulfan) was initially used in the treatment of certain solid tumors. Preclinical studies showed that it has a myeloablative effect on committed and non-committed stem cells. It has potent im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 76 publications
(136 reference statements)
4
68
2
Order By: Relevance
“…18 Structurally it is similar to BU. Unlike BU, it is water soluble and easy to reconstitute and administer intravenously.…”
Section: Novel Conditioning Regimenmentioning
confidence: 80%
“…18 Structurally it is similar to BU. Unlike BU, it is water soluble and easy to reconstitute and administer intravenously.…”
Section: Novel Conditioning Regimenmentioning
confidence: 80%
“…Probably, TREO provides lower organ toxicity than busulfan, especially hepato-, pulmo-, and neurotoxicity. One hypothesis that needs experimental verification assumes that because of lower lipophilicity of TREO compared with busulfan, the former achieves lower concentrations in those key organs and, consequently, is less toxic (Główka et al, 2010;Danylesko et al, 2012;Shimoni et al, 2012). The underlying mechanism of potentially low neurotoxicity of TREO appears particularly important for infants, as maturity of their blood-brain barrier (BBB) is still unknown (Saunders et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies demonstrated that treosulfan has intense activity against several malignancies. 27 The combination of fludarabine and treosulfan (FT) has been introduced over the last few years as a relatively dose-intensive regimen with favorable toxicity, mostly in patients with myeloid malignancies (reviewed in Danyelsko et al 28 ). We have compared FT with busulfan based RIC or MAC regimens in patients with AML and myelodysplastic syndromes.…”
Section: Introductionmentioning
confidence: 99%